Manajemen Dakwah dalam Meningkatkan Kualitas Jamaah Masjid Nurul Inayah di Kecamatan Bandung Kidul Kota Bandung - Muhammad Ridha Arsy; Rodliyah Khuza'i; Malki Ahmad Nasir (Bandung Conference Series: Islamic Broadcast Communication, 2023)
Abstract. Da'wah management is a form of effort in managing and delivering da'wah in order to achieve the targeted objectives acceptably, so that this effort of improving the quality of the congregation of the mosque has to be arranged in an organized and directed activity program. This research aims first is to an uncover the role of da'wah management in improving the quality of congregation at Nurul Inayah Mosque, second is to an uncover the efforts of the administrator of Nurul Inayah Mosque in improving the quality of the congregation; and last is to an uncover the supporting and inhibiting factors at the Administrator of Nurul Inayah Mosque in improving the quality of the congregation. This research employs the management theory through the functions of planning, organizing, actuating, and controlling. This study uses a qualitative method with a descriptive approach, while the data are collected through observations, interviews, and documentation. The research has found that the da'wah management at the administrator of Nurul Inayah Mosque cannot be separated from the functions of management in doing the activity program of the mosque. The efforts are including that are taking care of the mosque's facilities, creating schedules for those who deliever in the messages Friday Prayers, and doing congregation's development through Islamic studies which are conducted regularly. Abstrak. Manajemen dakwah adalah sebuah bentuk usaha dalam mengatur dan mengantarkan dakwah agar tepat sasaran mencapai tujuan yang diharapkan, sehingga usaha meningkatkan kualitas jamaah masjid ini mesti tersusun dalam program kegiatan yang teratur dan terarah. Penulis melakukan penelitian bertujuan untuk : mengetahui peran manajemen dakwah dalam meningkatkan kualitas Jamaah Masjid Nurul Inayah, mengetahui upaya pengurus Masjid Nurul Inayah dalam meningkatkan kualitas jamaah, dan mengetahui faktor pendukung dan faktor penghambat pengurus Masjid Nurul Inayah dalam meningkatkan kualitas jamaah. Penelitian ini menggunakan Teori Manajemen melalui fungsi planning, organizing, actuating, dan controlling. Adapun metode yang digunakan adalah deskriptif-analitis. Sedangkan teknik pengumpulan data melalui observasi, wawancara, dan dokumentasi. Alhasil penelitian ini didapatkan : bahwa manajemen dakwah pengurus Masjid Nurul Inayah tidak terlepas dari fungsi-fungsi manajemen dalam melakukan program kegiatan masjid, upaya yang dilakukannya adalah perawatan fasilitas masjid, membuat jadwal khotib shalat Jum’at, dan melakukan pembinaan jamaah melalui kajian yang dilakukan secara rutin.